2022
DOI: 10.1186/s12871-022-01869-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive end-expiratory pressure on pulmonary compliance and pulmonary complications in patients undergoing robot-assisted laparoscopic radical prostatectomy: a randomized control trial

Abstract: Background To observe the effects of different positive end-expiratory pressure (PEEP) ventilation strategies on pulmonary compliance and complications in patients undergoing robotic-assisted laparoscopic prostate surgery. Methods A total of 120 patients with the American Society of Anesthesiologists Physical Status Class I or II who underwent elective robotic-assisted laparoscopic prostatectomy were enrolled. We randomized the patients divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…During mechanical ventilation, PEEP levels usually do not exceed 5 cmH 2 O, which can be not sufficient to avoid lung atelectasis and prevent VILI [22]. Previous studies suggested to select PEEP achieving the maximal respiratory system compliance, the lower driving pressure or according to the intrabdominal pressure [9,22,[30][31][32]. When PEEP was individualized, resulting in levels between 12-14 cmH 2 O, arterial oxygenation and respiratory system compliance were higher compared to a lower fixed level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During mechanical ventilation, PEEP levels usually do not exceed 5 cmH 2 O, which can be not sufficient to avoid lung atelectasis and prevent VILI [22]. Previous studies suggested to select PEEP achieving the maximal respiratory system compliance, the lower driving pressure or according to the intrabdominal pressure [9,22,[30][31][32]. When PEEP was individualized, resulting in levels between 12-14 cmH 2 O, arterial oxygenation and respiratory system compliance were higher compared to a lower fixed level (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging and responding to this fundamental physical principle is crucial, as elevated IAP is associated with various negative effects. In comparison, intra-abdominal hypertension (IAH), i.e., an abdominal pressure above 12 mmHg, is a well-known and acted upon clinical condition in critically ill patients that increases morbidity and mortality through decreased abdominal organ perfusion and increased pressure transmitted to other body organs [26][27][28][29][30][31][32]. Indeed, a raised IAP can displace the diaphragm upward, thus causing a compression of the intrathoracic content that leads to increased transpulmonary pressure and decreased cardiac venous return [33].…”
Section: Pneumoperitoneum Effects and The Pressure-volume Derivativementioning
confidence: 99%